Penelitian tentang Penanganan dan Estimasi Biaya Perbaikan Kerusakan Jalan Menggunakan Metode Bina Marga dan SDI (Studi Kasus: Jalan Ir. Moh. Taher, Lueng Bata, Kota Banda Aceh) - Nadhila, Putri; Faisal, Ruhdi; Sugiarto, Sugiarto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
Ir. Moh. Taher street, Lueng Bata, Banda Aceh City is a primary collector road with provincial road status with a total length of 3.32 km and a width of 6 m. The road section that is the object of research is 1.5 km long from the Lueng Bata intersection to the Aceh Besar border. This section of road has a high level of traffic, because there are three government agency offices and two schools located along the road. As a result, road conditions become damaged and have an impact on the smooth running of road users' activities. This research aims to determine the type of road damage using the Highways and Surface Distress Index (SDI) method as well as handling and estimating the cost of repairing the damage. Data collection for this research is in the form of an average daily traffic survey (LHR) and a road damage survey which is divided into 100 m per segment for a total of 15 segments. The types of road damage that occur on this road section are cracks, grooves, patches, holes, surface roughness and sinking. With the most dominant percentage of damage being grooves 13.57% and holes 9.82%. Next, the data is processed and analyzed to determine appropriate treatment and a budget plan (RAB) for repairs is calculated. Using the Bina Marga method, the estimated cost required is IDR 1,335.8511.000. This method includes handling reconstruction along 100 meters (1 segment), handling overlay along 400 meters (4 segments), and routine maintenance 1 km (10 segments). For the SDI method, the estimated cost required is IDR 948.823.000 covers reconstruction handling of 100 meters (1 segment) and routine maintenance of 1.4 km (14 segments).